2004
DOI: 10.1128/jb.186.19.6536-6543.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the Escherichia coli O157, O111, and O55 O-Antigen Gene Clusters with Those of Salmonella enterica and Citrobacter freundii , Which Express Identical O Antigens

Abstract: Escherichia coli O157, Salmonella enterica O30, and Citrobacter freundii F90 have identical O-antigen structures, as do E. coli O55 and S. enterica O50. The O-antigen gene cluster sequences for E. coli O157 and E. coli O55 have been published, and the genes necessary for O-antigen biosynthesis have been identified, although transferase genes for glycosidic linkages are only generic and have not been allocated to specific linkages. We determined sequences for S. enterica O30 and C. freundii F90 O-antigen gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 29 publications
(29 reference statements)
2
53
0
Order By: Relevance
“…These included four strains belonging to the O14 and O57 serogroups, for which specific primers were not designed. It is known that Salmonella enterica and Citrobacter freundii share similar but sequence-diversified O-AGCs with E. coli O157, O111, and O55 but produce O antigens that are identical to those produced by E. coli (18). Plainvert et al (19) showed that there are two types of O-AGCs in E. coli O45 strains; one type is related to intestinal pathogenic E. coli such as STEC, and the other is related to extraintestinal pathogenic E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…These included four strains belonging to the O14 and O57 serogroups, for which specific primers were not designed. It is known that Salmonella enterica and Citrobacter freundii share similar but sequence-diversified O-AGCs with E. coli O157, O111, and O55 but produce O antigens that are identical to those produced by E. coli (18). Plainvert et al (19) showed that there are two types of O-AGCs in E. coli O45 strains; one type is related to intestinal pathogenic E. coli such as STEC, and the other is related to extraintestinal pathogenic E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Three Salmonella O-antigen structures are known to be shared with other enteric organisms: Salmonella serogroup O35 and E. coli O111 have the same antigen structure, as do Salmonella serogroup O50 and E. coli O55, and Salmonella serogroup O30, E. coli O157, and Citrobacter freundii F90. The respective rfb gene clusters from Salmonella, E. coli, and C. freundii with identical O antigens are, in turn, also highly related to one another (50,56).…”
mentioning
confidence: 99%
“…The antigenic differences among the 46 Salmonella O serogroups are due mainly to genetic variation in their respective rfb gene clusters (58). The rfb gene clusters from 15 Salmonella serogroups have been characterized or sequenced: A (32), B (24), C 1 (28), C 2 (5), D 1 (32), D 2 (9), D 3 (9), E (54), O6,14 (18), O17 (19), O18 (19), O35 (56), O30, O50 (50), and O54 (26). The O antigens of serogroups A, B, C 2 , D 1 , D 2 , D 3 , and E have related structures, and their rfb regions are related.…”
mentioning
confidence: 99%
“…There are several pairs of Salmonella and E. coli strains that are known to have identical or closely related O antigen organizations, such as serotype O35 and E. coli O111, serotype O50 and E. coli O55, and serotype O30 and E. coli O157 (33,36). Nonetheless, their gene clusters at the nucleotide level are divergent, and the average identities of wzx and wzy are 70 and 63%, respectively, which is enough difference to discriminate them from each other.…”
Section: Discussionmentioning
confidence: 99%